Practical Application of N2N Technology in Virtual LAN Management System - Wu, Zhen; Song, Qingqing (Journal of Computer Technology and Applied Mathematics, 2024)
Due to the impact of the COVID-19 epidemic and related policies, remote collaboration technology that is not limited by geographical location has begun to be widely used. Among them, virtual LAN, as an important remote collaboration technology, has received widespread attention. This study is based on N2N peer-to-peer virtual private network technology, utilizing its advantages of high performance, high convenience, and direct traffic connection between nodes under specific conditions, and making it the core technology for constructing and accessing virtual local area networks. In this study, we introduced the application of N2N technology in virtual LAN management systems, and verified the feasibility of applying N2N technology to virtual LAN management systems through the design of the overall system architecture and various parts. Finally, we proposed a solution based on N2N technology that integrates LAN construction, network partitioning, and user management.